Prevalence of Congenital Anomalies in Iran: A Review Article - Soudabeh VATANKHAH; Mina JALILVAND; Samaneh SARKHOSH; Mina AZARMI; Mohammad MOHSENI (Tehran University of Medical Sciences, 2017)
Background: Congenital anomalies are considered as main causes of disability and mortality among children in developing and developed countries. Expenditures of hospitalization and treatment procedures for these children impose a large burden on health system and their families. This study aimed to review the prevalence of congenital anomalies among infants in Iran. Methods: The review of studies was conducted through searching databases including IranMedex, SID, Magiran, Scopus, and PubMed. Descriptive and cross-sectional studies investigating on the prevalence of congenital anomalies among infants were included into the study. Hand search for some related journals and websites was done. The list of studies' references was reviewed. The data were analyzed using the CMA 2 software. Results: Of 455 studies, 27 studies were included into the meta-analysis study. The studies were conducted between 1992 and 2014.The overall prevalence of congenital anomalies among infants was estimated to be 2.3%. The overall prevalence rates, in terms of gender, were estimated to be 3% in boys and 2% in girls. While the highest prevalence rates were related to musculoskeletal anomalies (27.5%), skin anomalies (19.7%) and genitourinary system anomalies (15.8%), the lowest prevalence rate was related to respiratory system (1.82%) Conclusion: The prevalence of congenital anomalies among infants in Iran is high. In order to reduce the rates of these anomalies and complications resulted from them, coping and preventive strategies such as the necessity of genetic counseling particularly in consanguineous marriages seem to be appropriate solutions.